DEVELOPMENT OF AN EXERCISE MODEL USING RESISTANCE BANDS FOR POST-SOCCER INJURY RECOVERY - Perdana, Glady Sukma; Makadada, Fredrik Alfrets (Olympus : Jurnal Pendidikan Kesehatan dan Rekreasi, 2025)
This study aims to develop a training model product utilizing resistance bands for post-injury rehabilitation in football players, which can be employed by athletes recovering from injuries. The research method applied in this study follows the Research and Development framework, adapting Sugiyono's steps into seven stages: (1) Identifying potential and problems, (2) Collecting information, (3) Designing and creating the initial product, (4) Validating the design, (5) Revising, (6) Finalizing the product, and (7) Product testing. The training program book that employs resistance bands for post-injury recovery was validated by one content expert and one media expert. It was tested with three coaches and twelve sports coaching students, totaling fifteen participants. The data obtained were analyzed descriptively and quantitatively. Quantitative data was derived from questionnaires, which were expressed as percentages to indicate the product's feasibility level. The results of the development research for the training book using resistance bands in post-injury rehabilitation for football players revealed a content validity score of 88.3% from the content expert, indicating it is feasible. The media expert's validation yielded a score of 85.6%, categorizing it as highly feasible. During product testing, the overall assessment resulted in a score of 86.9%, placing it in the "Highly Feasible" category. Therefore, the developed product of this training manual is deemed appropriate for use. Consequently, the model of training using resistance bands for post-injury recovery in football, packaged as a guideline book, is suitable for use as a learning medium that is easy to understand and can be directly practiced.